Finance and Development, December 1966. (Finance and Development; Finance and Development ;, 1966)
This paper discusses the 1966 Annual Meetings of the IMF and of the World Bank and its affiliates, the International Development Association (IDA) and the International Finance Corporation. The annual meetings were held in September in Washington. The widespread shortage of capital and rising interest rates were described as posing problems for the Bank's own borrowings as well as for developing countries. Mr. George D. Woods, the President, stressed the allied problem of the urgent need for a substantial replenishment of the resources available to IDA.